2004
DOI: 10.1143/jjap.43.6692
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Piezoelectric Properties of Potassium Niobate Single Crystals by Domain Engineering

Abstract: The engineered domain configuration was induced into potassium niobate (KNbO3) crystals, and the piezoelectric properties were investigated as a function of domain size. First, single-domain treatment was investigated, and a combination of chemical etching and 2-step electric poling treatment was effective. Using the single-domain crystals, all piezoelectric related constants were determined. On the basis of these piezoelectric constants, the d 31 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
51
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(56 citation statements)
references
References 32 publications
5
51
0
Order By: Relevance
“…Moreover, the intrinsic contribution, as measured along the non polar ͓001͔ C poling direction of each domain-engineered crystal, is also expected to increase as the first order ferroelectric-ferroelectric phase transition is approached. 25 There is significant evidence that the presence, rather than motion, of domain walls in domain-engineered barium titanate and potassium niobate leads to an increase piezoelectric response, [35][36][37][38][39] especially when the domain structure becomes very fine ͓Ͻ10 m ͑Ref. 38 and 39͔͒.…”
Section: -4mentioning
confidence: 99%
“…Moreover, the intrinsic contribution, as measured along the non polar ͓001͔ C poling direction of each domain-engineered crystal, is also expected to increase as the first order ferroelectric-ferroelectric phase transition is approached. 25 There is significant evidence that the presence, rather than motion, of domain walls in domain-engineered barium titanate and potassium niobate leads to an increase piezoelectric response, [35][36][37][38][39] especially when the domain structure becomes very fine ͓Ͻ10 m ͑Ref. 38 and 39͔͒.…”
Section: -4mentioning
confidence: 99%
“…[8][9][10][11][12] Domain size engineering is another important approach for obtaining enhanced piezoelectric properties in lead free piezoelectric single crystals. [13][14][15][16][17][18] The experimental results revealed that the enhanced piezoelectric coefficient was associated with high domain wall density, for example, the piezoelectric coefficient d 31 was found to increase from À98 pC/N to À230 pC/N with domain sizes of 40 lm and 5.5 lm in BaTiO 3 crystals, 15 while the piezoelectric coefficient d 33 was predicted to be greatly increased with nano-size domain configuration. 17 The theoretical simulation indicated that the piezoelectric coefficient was enhanced by reducing domain size, while an enhancement of piezoelectric coefficient in BaTiO 3 crystals with 90 twinned domain configuration was predicted using Ginzburg-LandauDevonshire model.…”
Section: Introductionmentioning
confidence: 96%
“…Following the rediscovery of their very high piezoelectric coefficients for rhombohedral or orthorhombic compositions oriented along the nonpolar ͓001͔ C ͑C: pseudocubic͒ direction, 1 much work has concentrated on the concept of domain engineering 2 not only in these materials [3][4][5][6][7] but in simpler perovskite crystals as well. [8][9][10] A good definition of "domain engineering" is that given by Bell: 2 A domain-engineered crystal is one which has been poled by the application of a sufficiently high field along one of the possible polar axes of the crystal other than the zerofield polar axis, creating a set of domains in which the polarizations are oriented such that their angles to the poling direction are minimized. In a perovskite material there are therefore three possible sets of poling directions ͗111͘ C , ͗101͘ C , and ͗001͘ C ͑if monoclinic phases are ignored͒.…”
Section: Introductionmentioning
confidence: 99%
“…9,18 However, these domain-wallrelated effects will not be discussed here. Since intrinsic effects will be dominant in most cases, calculations of piezoelectric coefficients along nonpolar directions based on single-domain data are still useful in predicting the properties of domain-engineered crystals.…”
Section: Introductionmentioning
confidence: 99%